Necro-inflammatory response of pancreatic acinar cells in the pathogenesis of acute alcoholic pancreatitis - Gu, Haitao; Werner, Jens; Bergmann, Frank; Büchler, Markus W.; Fortunato, Franco (Cell death & disease, 2013)
The role of pancreatic acinar cells in initiating necro-inflammatory responses during the early onset of alcoholic acute pancreatitis (AP) has not been fully evaluated. We investigated the ability of acinar cells to generate pro- and anti-inflammatory mediators, including inflammasome-associated IL-18/caspase-1, and evaluated acinar cell necrosis in an animal model of AP and human samples. Rats were fed either an ethanol-containing or control diet for 14 weeks and killed 3 or 24 h after a single lipopolysaccharide (LPS) injection. Inflammasome components and necro-inflammation were evaluated in acinar cells by immunofluorescence (IF), histology, and biochemical approaches. Alcohol exposure enhanced acinar cell-specific production of TNFα, IL-6, MCP-1 and IL-10, as early as 3 h after LPS, whereas IL-18 and caspase-1 were evident 24 h later. Alcohol enhanced LPS-induced TNFα expression, whereas blockade of LPS signaling diminished TNFα production in vitro, indicating that the response of pancreatic acinar cells to LPS is similar to that of immune cells. Similar results were observed from acinar cells in samples from patients with acute/recurrent pancreatitis. Although morphologic examination of sub-clinical AP showed no visible signs of necrosis, early loss of pancreatic HMGB1 and increased systemic levels of HMGB1 and LDH were observed, indicating that this strong systemic inflammatory response is associated with little pancreatic necrosis. These results suggest that TLR-4-positive acinar cells respond to LPS by activating the inflammasome and producing pro- and anti-inflammatory mediators during the development of mild, sub-clinical AP, and that these effects are exacerbated by alcohol injury.
Gesehen am 16.02.2021